Crossbreeding Ayrshire, Friesian, and Sahiwal cattle for milk yield and preweaning traits of progeny in the semiarid tropics of Kenya - Thorpe, W.R.; Kang'ethe, P.; Rege, J.E.O.; Mosi, R.O.; Mwandotto, B.A.J.; Njuguna, P. (American Dairy Science Association, 1993)
Individual and maternal additive genetic and heterotic effects were estimated for preweaning, reproductive, and lactation traits of the Sahiwal breed and its crosses with Bos taurus (Ayrshire and Friesian). The individual additive genetic breed effect influenced all cow traits except annual milk yield, and the maternal additive genetic effect influenced all yield traits. The individual and maternal genetic effects between B. taurus and Sahiwal breeds for lactation milk yield were 746 and -601 kg, respectively. Individual heterosis for lactation milk yield of 73 kg (5 percent), estimated using the mean of the reciprocal F1 crosses, was not significant but increased to 374 kg (28 percent) when estimated using only the F1 cross sired by B.taurus, showing the important influence of maternal effects. Individual additive genetic effects influenced preweaning daily gain and weaning weight. Maternal additive genetic and heterotic effects affected birth weight, and individual heterosis significantly influenced all calf traits. Maternal additive genetic effects may have biased the estimation of individual heterosis for milk yield in other tropical studies. When stratification is not possible or when reproductive rates are low, two-breed rotational crossbreeding is an efficient system to exploit additive and nonadditive genetic variation for tropical dairy production.